The impact of political events on the kwacha: a focus on elections - Lungu, Chozi Dickens (Research of GSB, 2018)
Political events can be described as events that affect a country's economic and regulatory environment. Such events may include changes in monetary and fiscal policy, changes in trade and foreign policy, cabinet reshuffles and changes in government. In emerging markets, political events can affect asset prices because of the impact they can have on foreign sentiment and investor confidence. Elections in particular can cause considerable uncertainty which can lead to herding behavior by investors, if outcomes do not reflect prior predictions. Unfavorable election results can lead to currency depreciation, stock market crashes and economic deterioration as investors change their expectations and demand higher premiums due to the perceived increase in sovereign as well as currency risk. This research focuses specifically on the effect of presidential elections on the exchange rate between U.S. Dollar and Zambian Kwacha. The study employs the event study methodology by dividing elections into two periods and these are; a month leading to the election and another month after the elections. The study will examine three distinct presidential elections that occurred in Zambia in 2011, 2015 and 2016 respectively. The research uses daily time series data for the periods September 2011, January 2015 and August 2016. The methodology makes use of the currency pair's daily mid-rate as inputs to the market model. The market model was used to calculate average abnormal returns and cumulative average abnormal returns. Test of significance was conducted using t-test with 5 percent level of significance using a two-tailed test. The results of the t-test show that political events represented by the presidential elections had a statistically significant effect on the Kwacha, with noteworthy observations concentrated around the days following the event. The study recommends that key policy makers and stakeholders should place more emphasis in ensuring a healthy and safe political environment in the country. Investors should also be cautioned against viewing emerging markets as one homogenous group. The results in this study are unique to Zambia, which has had a history of holding peaceful (and arguably), free and fair elections since becoming a multi-party democracy in 1991.